Typification of names in the genus Camellia (Theaceae) - Zhao, Dongwei; Parnell, John A. N.; Hodkinson, Trevor R. (Phytotaxa, 2017)
Nomenclatural types for 18 names actually belonging to the genus Camellia are designated here. The following names are lectotypified: Camellia caudata, C. indochinensis, Dankia langbianensis, Thea bachmaensis, T. brachystemon, T. confusa, T. connata, T. corallina, T. fleuryi, T. gaudichaudii, T. gilbertii, T. krempfii, T. laotica, T. nematodea, T. nervosa, T. pleurocarpa, T. taliensis and T. tonkinensis.